ANALISIS PRAKTIK MANAJEMEN LABA SEBELUM DAN SESUDAH PEMBERLAKUAN UU NO. 36 TAHUN 2008 - Yustina, Yustina; Rahardjo, Hartono; Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2013)
A change in corporate income tax rates in 2008 were effected from January 1, 2009 will lead to an indication of earnings management by the company to obtain tax savings. Therefore, this study aimed to analyze whether the company's conduct earn-ings management in response to changes in corporate income tax rates. In addition, this study also analyze factors that affecting earnings management by companies. Variable’s research that used in this study are discretionary accrual (DA), net of deferred tax liabilities (NDTL), debt level (DEBT), firm size (SIZE), and managerial ownership (MGTOWN). The research design is quan-titative. The object of research is a manufacturing company listed on the Indonesia Stock Exchange with the study period of one year before and two years after the change of income tax rate that is year 2008-2010. Source data obtained from financial state-ments published by the Indonesia Stock Exchange and the Indonesian Capital Market Directory. Techniques of data analysis was performed with two sample t-test and multiple linear regression analysis. The test results showed that the company does not un-dertake earnings management in response to changes income tax rate for obtain the tax savings. The test results also show that earnings management is done by the company is affected by NDTL. NDTL significant positive impact to earnings management while DEBT, SIZE, and MGTOWN no significant effect to earnings management.